2010
DOI: 10.1016/j.annemergmed.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Self-Triage of Influenza-Like Illness During the 2009 H1N1 Influenza Pandemic

Abstract: The sudden emergence of 2009 H1N1 influenza in the spring of that year sparked a surge in visits to emergency departments in New York City and other communities. A larger, second wave of cases was anticipated the following autumn. To reduce a potential surge of health system utilization without denying needed care, we enlisted the input of experts from medicine, public health, nursing, information technology, and other disciplines to design, test, and deploy clinical algorithms to help minimally trained health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 10 publications
0
42
0
7
Order By: Relevance
“…Decision aids, like the strategy for off-site rapid triage, a web-based decision aid designed in response to the 2009 H1N1 influenza pandemic, aim to provide better informed decision-making during times of medical crisis (Kellermann et al, 2010). Dolan et al (2015) demonstrated that user decision outcomes varied with the presentation of labels during decision aid use, suggesting that decision aids need to consider conscious and unconscious biases to be maximally effective.…”
Section: Discussionmentioning
confidence: 99%
“…Decision aids, like the strategy for off-site rapid triage, a web-based decision aid designed in response to the 2009 H1N1 influenza pandemic, aim to provide better informed decision-making during times of medical crisis (Kellermann et al, 2010). Dolan et al (2015) demonstrated that user decision outcomes varied with the presentation of labels during decision aid use, suggesting that decision aids need to consider conscious and unconscious biases to be maximally effective.…”
Section: Discussionmentioning
confidence: 99%
“…34 Standards facilitating patient downloading and sharing of their EHR information, 35 combined with the ubiquity of smart mobile devices, may enable powerful platforms for public health surveillance, tailored alerting (e.g., notifying asthmatics of air quality problems), and personal health decision support (e.g., when to seek care). 36 Crowdsourcing has already assisted disaster and outbreak management, 37 and many people value opportunities to communicate about potential hazards and events. 38 Online information from outbreak "cases" may replace much future public health interviewing (as it has replaced voice interactions for many purchases, travel reservations, and appointments).…”
Section: Engaging the Public And The Digital Dividementioning
confidence: 99%
“…25 This study was limited by the wide spectrum of disease associated with influenza infection because the course tends to be less predictable, with higher morbidity and mortality. Unlike influenza, pharyngitis is usually nonurgent and can typically wait for evaluation without concern for rapid clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%